2021
DOI: 10.1097/pts.0000000000000925
|View full text |Cite
|
Sign up to set email alerts
|

Root Cause Analysis Using the Prevention and Recovery Information System for Monitoring and Analysis Method in Healthcare Facilities: A Systematic Literature Review

Abstract: ObjectivesUnintended events (UEs) are prevalent in healthcare facilities, and learning from them is key to improve patient safety. The Prevention and Recovery Information System for Monitoring and Analysis (PRISMA)-method is a root cause analysis method used in healthcare facilities. The aims of this systematic review are to map the use of the PRISMA-method in healthcare facilities worldwide, to assess the insights that the PRISMA-method offers, and to propose recommendations to increase its usability in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Driessen and colleagues recently presented a literature review on the use of the Prevention and Recovery Information System for Monitoring and Analysis (PRISMA) method for health care institutions [ 10 ]. The application of PRISMA provides a root cause analysis of factors such as unplanned ICU admissions [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Driessen and colleagues recently presented a literature review on the use of the Prevention and Recovery Information System for Monitoring and Analysis (PRISMA) method for health care institutions [ 10 ]. The application of PRISMA provides a root cause analysis of factors such as unplanned ICU admissions [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another strength of this study is that patients’ medical records were analyzed completely and objectively by trained multidisciplinary medical professionals, which enabled the acquisition of diverse insights concerning unplanned events that involve different aspects of healthcare and different healthcare professionals [ 29 , 54 ]. The PRISMA method itself is another strength of this study, as it provides in-depth insight into healthcare interventions on a larger scale [ 54 ], and systematic analysis of unplanned events could indicate organizational safety flaws [ 54 ]. The reliability was ensured by the individual assessment of data by qualified and PRISMA trained medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Human and organizational factors are known to be the most frequently identified causes in SE or adverse event studies. 8 , 31 , 32 Not many contributing factors were identified that related to the physical and external environment. A possible explanation could lie in the fact that traditional root cause analysis methods do not or only limitedly address these domains and thus may be underreported in the SE reports.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregated cross-hospital SE analysis using the GAM indicates that a majority of contributed factors were related to the persons and organization domains. Human and organizational factors are known to be the most frequently identified causes in SE or adverse event studies 8,31,32 . Not many contributing factors were identified that related to the physical and external environment.…”
Section: Discussionmentioning
confidence: 99%